A NATUREZA NA CIDADE: UMA ABORDAGEM A PARTIR DA PERCEPÇÃO DA POPULAÇÃO ACERCA DO JARDIM BOTÂNICO DE CURITIBA (PR) / The nature in the city: a boarding from the perception of the population concerning the botanical garden of Curitiba (PR) - Márcio Luís Hassler (Sociedade & Natureza)
Each more difficult time becomes, nowadays, to dissociate city and nature, therefore the urbanizationprocess influences and is influenced by entorno of its area of occupation, constituting half integratedwhich if would not have to apply no link to if elaborating studies of problematic socio environmentalurbans. From the concern in analyzing the relations established between the society and nature itis questioned: ‘What it is “Nature”? ‘Very probably they appear, to leave of this investigation,some answers, related with the object of study or still with the problematic one of approach. Whenof the analysis to try to answer to this question it is had that to lead in account that the directionof Nature is extremely ample and possesss diverse definitions. With this the problematic one indefining the “Nature” appears as such, at a moment where if it speaks widely in “defending theenvironment” of the aggressions human beings, or either, of the aggressions of the proper society.The geographic boarding of the conception of “nature” in the city if places as objective main ofthis work, that if based on the perception to carry through its verifications. In this context if it inserts the Botanical Garden of Curitiba, that if it reflects as “Nature” in the City, seen of diverseforms for a group of people of Curitiba.